2001
DOI: 10.1046/j.1365-2923.2001.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a questionnaire to evaluate the effectiveness of evidence-based practice teaching

Abstract: The results of this validation study indicate that the developed questionnaire is a satisfactory tool with which to evaluate the effectiveness of EBP teaching interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 4 publications
2
72
0
1
Order By: Relevance
“…Our results are consistent with those of the Fresno test of competence in EBM and with the Swiss cross-sectional study conducted among medical researchers by Perneger et al [9,14]. Furthermore, using a questionnaire assessing the effectiveness of evidence-based practice teaching, Taylor et al [21] showed that significant differences in the knowledge and attitude scores of novices compared to experts confirmed its discriminatory validity. We did not analyze skills in EBM as examined by the Fresno test [14] or the Berlin questionnaire [22].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with those of the Fresno test of competence in EBM and with the Swiss cross-sectional study conducted among medical researchers by Perneger et al [9,14]. Furthermore, using a questionnaire assessing the effectiveness of evidence-based practice teaching, Taylor et al [21] showed that significant differences in the knowledge and attitude scores of novices compared to experts confirmed its discriminatory validity. We did not analyze skills in EBM as examined by the Fresno test [14] or the Berlin questionnaire [22].…”
Section: Discussionsupporting
confidence: 92%
“…24 Eigenvalues of !1 and factor loading scores !0.4 were used to select those factors that explained the most total variance. [23][24][25][26][27] Factor loading scores greater than 0.4 demonstrate a strong relationship within the factor. The Kaiser-Meyer-Olkin measure was used to determine if the sample was adequate for factor analysis.…”
Section: Instrumentationmentioning
confidence: 99%
“…A recent study by Taylor et al 39 was published after our data collection and analysis. They developed a questionnaire and measured its validity in evaluating the effectiveness of EBHC teaching.…”
Section: Ideal Study Designmentioning
confidence: 99%